Accrual Anomaly in Indonesia (Empirical Study of Companies Registered in Indonesia’s Stock Exchange) - Elbert Ludica Toha; Siti Nurwahyuningsih Harahap (The Indonesian Journal of Accounting Research, 2014)
Abstract: Many studies have found a reverse correlation between the levels of accruals and subsequent abnormal stock return on the US market, which is caused by investor’s failure in predicting the future earnings using the cash and the accrual components. Investors overweight the accrual component. This relationship is considered as an anomaly since it is not a corresponding with the efficient market hypothesis, in which the investors should not overweight accrual component. This research aims to detect accrual anomalies to the companies registered in the Indonesia stock exchange. The sample used in this study is a list of companies on the Indonesia Stock Exchange with a total of companies are 121 companies. The result shows that there is accrual anomaly in Indonesia although it is slightly different from the US market.Abstrak: Banyak penelitian telah menemukan korelasi terbalik antara tingkat akrual dan pengembalian saham abnormal berikutnya di pasar AS, yang disebabkan oleh kegagalan investor dalam memprediksi pendapatan masa depan menggunakan uang tunai dan komponen akrual. Investor kelebihan berat komponen akrual. Hubungan ini dianggap sebagai anomali, karena itu tidak sesuai dengan hipotesis pasar yang efisien, di mana para investor tidak harus kelebihan berat badan komponen akrual. Penelitian ini bertujuan untuk mendeteksi anomali akrual terhadap perusahaan yang terdaftar di bursa efek Indonesia. Sampel yang digunakan dalam penelitian ini adalah daftar perusahaan di Bursa Efek Indonesia dengan total perusahaan adalah 121 perusahaan. Hasilnya menunjukkan bahwa ada anomali akrual di Indonesia meskipun sedikit berbeda dengan pasar AS.